Evaluation of recitation program in mathematics learning at SMAN 1 Sindangwangi - Reza Oktiana Akbar; Budi Manfaat; Ridwan Ridwan (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2023)
Despite the implementation of the recitation program in mathematics learning at SMAN 1 Sindangwangi which has been going on for quite a long time, the success of this program has not been measured yet. This research aimed to determine the context, input, process, and product of the mathematics learning recitation program. The method used in this research was descriptive qualitative. This evaluation research adopted the CIPP model which consists of four aspects, namely context, input, process, and product. The evaluation results of the four aspects show good criteria. The good context aspect of the recitation program is shown by the quality of the learning environment and the alignment between the implementation background and program objectives. The input aspect of the program is considered good seen from the suitability of the curriculum aspects with the topics and subtopics being recited, teachersâ€™ academic qualifications, and the adequate infrastructure. The process aspect is categorized as good indicated by the positive impact on students' understanding, the quality of teachers, and the active response of students in the learning activities. Finally, the good product aspect is seen from studentsâ€™ quite good learning outcomes exceeding the specified minimum completion criteria.Keywords: CIPP, program evaluation, recitation programÂ